Rancang Bangun Sistem Parkir Otomatis Menggunakan Arduino Uno dan Antarmuka GUI Berbasis Python - Muhamad Faridzqi Suryadi; Muhammad Sahal Anwar Hadi; Muhammad Saef Mubhaul Abbas; Shela Rahma Fitri; Novianti Ramadhani (Jurusan Teknik Elektro Universitas Trunojoyo Madura, 2025)
Conventional parking systems often cause problems such as long queues, delays in recording, and lack of efficiency in vehicle data management. Therefore, this study designed an automatic parking system using Arduino Uno combined with HC-SR04 ultrasonic sensors, servo motors, input buttons (push buttons), and a Python Graphical User Interface (GUI). When a vehicle is detected by the sensor, a 16x2 Liquid Crystal Display (LCD) will display a welcome message and instructions to the user to press the button to print a parking ticket. This system records the vehicle's entry time and generates a ticket with a unique Identification (ID) code and arrival time. All vehicle data is stored in a Comma-Separated Values (CSV) file to facilitate monitoring and calculation of parking fees when the vehicle exits. This system can calculate the total parking cost based on the duration of parking at the predetermined rate and display parking user data on the GUI. Based on testing, the system can detect vehicles at an effective distance of 5–15 cm using ultrasonic sensors, open and close the barrier using a servo motor in approximately 1–2 seconds, and print tickets via a thermal printer in less than 3 seconds. These results indicate that the developed system can operate automatically and efficiently, so that it has the potential to be a solution to reduce problems in manual parking management.